Molecular Mechanism of the Grid Gene Family Regulating Growth Size Heteromorphism in Cynoglossus semilaevis - Yaning Wang; Yadong Chen; Yang Liu; Songlin Chen (Animals)
There are obvious individual differences in the growth and development of Cynoglossus semilaevis, mainly due to female bias. We selected 500 female Cynoglossus semilaevis of different sizes for GWAS and transcriptome analysis to screen for differential genes. qPCR was performed to detect the expression of the genes in various tissues, and RNAi experiments were performed in testicular cells to knock down the grid1 and grid2 genes and transcriptome sequencing was performed to check the changes of the downstream genes. Grid gene was screened for the common genes by GWAS sequencing and transcriptome sequencing. In the QPCR results, the expression of the grid gene family was negatively correlated with fish size, and was slightly higher in males than in females; in the transcriptome results, the expression of shcbp1, sass6, cdca7, and gh was up-regulated, and the expression of igf1 was down-regulated. It is speculated that igf1 has an antagonistic effect on gh, which is deregulated when the grid gene family is knocked down. The grid gene family may affect the growth of individual Cynoglossus semilaevis through the gh-igf1 axis, which provides a basis for the study of the differences in the growth size of Cynoglossus semilaevis.